Battles of the new republic : a contemporary history of Nepal - Jha, Prashant, 1984- (Hurst & Company, 2014)
A personal attempt to explore the underlying processes that are at the heart of Nepal's transition from monarchy to republicanism, from Hindu kingdom to secularism, from a narrow hill-centric notion of nationalism to an inclusive sense of citizenship.